Зоогеографическое районирование Венгрии - Михайлов, В.А.; Татаринов, К.А. (Вестник зоологии, 1971)
The territory of Hungar y belongs to the European-Siberian subregion. Mountain
forest regions and plains are included into the West-European province, and central and
south-eastern parts of the Grea t Central Danubia n Plain — into the Steppe province.
Using the dat a of Soviet and Hungaria n zoologists and on the basis of characteristic of
the predominant zoocenoses and distribution of some dominating animal species within
the boundarie s of natura l landscapes, four zoogeographica l districts are distinguished with 11 plots in them.